Antioxidant and Mineral Content of Pitaya Peel Extract obtained using Microwave Assisted Extraction (MAE) - Norashikin, Mat Zain; Muhammad Azlan, Nazeri (AENSI Publishing, 2016)
Background: Microwave Assisted Extraction (MAE) was used to extract active compounds in pitaya peels by using water as a solvent. Pitaya peels can be seen as a potential form of fruit waste, especially in the food industry because its solution extraction can be applied as natural coloring and contained beneficial active compounds that have commercialize value. Besides, extraction can be a solution for minimizing wastes produced by food processing industry. These food wastes often contain several usable substances of high value including some that are beneficial for health. Objective:The aim of this study is to determine the total phenolic content (TPC), antioxidant activity and mineral content of pitaya peel extract solution. Results:The results indicate that antioxidant activity had a good correlation with phenolic content. Meanwhile, 14 out of 24 elements were identified, which are Ba, Ca, Cu, Cd, Fe, K, Mg, Mn, Na, Ni, Pb, Sr, Ti, and Zn. All mineral data were validated using the CCLASS software. Conclusion: MAE is the best optional equipment for extraction since the integrity of the active compound is still maintained.